Pelanggaran Etika dan Profesi Hukum Kasus Suap Hakim Ronald Tannur: Analisis Kritis terhadap Integritas Penegakan Hukum di Indonesia - Farbadi, Mayla Putri; Sianturi, Mouna Suez; Setiawan, Sekar Marchayu; Puteri, Rheyna Wisnu; Sirait, Priscila Hosiana Deandra; Sedyo, Nastiti Respati; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This case shows how three judges of the Surabaya District Court were involved in bribery practices in the case of Gregorius Ronald Tannur's release. This article examines the bribery case of Judge Ronald Tannur as a reflection of ethical and professional issues in the legal field in Indonesia. The focus of this research is on how the ethical violations and breaches of the legal profession's code of ethics in that case have undermined the integrity of the Indonesian judicial system. This violates the principles of judicial independence and integrity regulated in Law No. 48/2009 on Judicial Power. This research shows the systemic consequences of such violations, such as a decline in public trust in the judicial system, an increase in perceptions of injustice, and challenges to the advancement of democracy and the rule of law. In addition, this article offers solutions to prevent the issues. This includes improving the internal-external oversight system, implementing a meritocracy system for the appointment of judges, and incorporating continuous professional ethics education. The results of this study indicate that structural reforms in the Indonesian judicial system are crucial for restoring public trust and ensuring the integrity of law enforcement.